Functional Ceramic Coatings - Pietrzyk, Bozena; Miszczak, Sebastian (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Ceramic materials in the form of coatings can significantly improve the functionality and applications of other engineering materials. Due to a wide range of controllable features and various deposition methods, it is possible to create tailored substrate-coating systems that meet the requirements of modern technologies. Therefore, it is crucial to understand the relationships between the structures, morphology and the properties of ceramic coatings and expand the base of scientific knowledge about them. This book contains a series of fourteen articles which present research on the production and properties of ceramic coatings designed to improve functionality for advanced applications.